Manusia Berbasis Al-Quran Dalam Dimensi Filsafat Ilmu - Tamrin, Abu (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract:The paper discusses the creation of humans which is preceded by human terms: bashar (Ø¨Ø´Ø±), ins (Ø§Ù†Ø³), nas (Ù†Ø§Ø³). Humans are created by Allah in the best possible form from the soil, the essence of the soil, the weak nutmeg of water (semen). The word al-nafs in the Qur'an has a significant position as one of the key words for understanding humans. The substance in the expert view consists of physical substance and spiritual substance, the soul has to do with the heart and mind. The personality in contemporary literature is different from the Islamic Psychology which is sourced from the Koran. Verse of the Qur'an in detail explains mental health, among others: QS. Al-Qasas [28]: 77, QS. Al-Nahl [16]: 97, and QS. Ali Imran [3]: 104. The paper concludes with a conclusion that answers the formulation of the problem.Keywords: Human, Qur'an, Philosophy of ScienceÂ Abstrak:Makalah membahas penciptaan manusia yang didahului istilah manusia: basyar (Ø¨Ø´Ø±), ins (Ø§Ù†Ø³), nas (Ù†Ø§Ø³). Manusia diciptakan oleh Allah swt dalam bentuk sebaik-baiknya berasal dari tanah, sari tanah, nutfah air yang lemah (sari air mani). Kata al-nafs dalam Alqurâ€™n memiliki posisi signifikan sebagai salah satu kata kunci untuk memahami manusia. Substansi dalam pandangan ahli terdiri substansi jasmani dan substansi ruhani, jiwa ada hubungannya dengan hati dan akal. Kepribadian dalam literatur kontemporer berbeda dengan Psikologi Islam yang bersumber Alquran. Ayat Alquran secara rinci menjelaskan kesehatan mental antara lain: QS. Al-Qasas [28]: 77, QS. Al-Nahl [16]: 97, dan QS. Ali Imran [3]: 104. Makalah diakhiri dengan kesimpulan yang menjawab perumusan masalah.Kata kunci: Manusia, Alquran, Filsafat Ilmu